IMPACT OF Ki-67 AND E-CADHERIN EXPRESSION ON LYMPHOVASCULAR INVASION IN UPPER URINARY TRACT UROTHELIAL CARCINOMA - Krstić, Miljan (Vojnosanitetski pregled, 2015)
AIM: To investigate the correlation between lymphovascular invasion and immunohistochemical expression of two frequently routinely applied immunohistochemical biomarkers, Ki-67 and E-cadherin, in upper urinary tract urothelial carcinoma. MATERIALS AND METHODS: The specimens from 106 patients with upper urinary tract urothelial carcinoma who had undergone nephroureterectomy were analyzed for pathologic parameters and lymphovascular invasion, while Ki-67 and E-cadherin expression was assessed by immunohistochemistry. RESULTS: Ki-67 was overexpressed in 38% of the cases, while 45% of tumors demonstrated aberrant E-cadherin staining. The presence of lymphovascular invasion was significantly associated with tumor stage, grade, non-papillary growth, nodular invasion pattern, high Ki-67 labeling index and altered E-cadherin expression. Analyzing logistic regression models, we have shown that tumor properties such as stage, grade, growth and invasion pattern (p<0.001), as well as the expression of Ki-67 and E-cadherin (p<0.001) significantly predicted the presence of lymphovascular invasion. In the first model, only solid tumor architecture (p<0.05) and nodular invasion pattern (p<0.05) were significant predictors of lymphovascular invasion. In the second model, Ki-67 expression was found to improve the prediction of lymphovascular invasion (p<0.05). CONCLUSION: Our results suggest that Ki-67 overexpression is an independent predictor of lymphovascular invasion in upper urinary tract urothelial carcinoma, indicating the progression of the disease. E-cadherin staining adds no valuable information to lymphovascular invasion probability assessment. This emphasizes the importance of Ki-67 staining of upper urinary tract urothelial carcinoma sections in routine pathological practice. Patients with Ki-67 overexpression, especially in solid tumors with nodular invasion, should be monitored more closely after surgery.